The fruit fly Drosophila melanogaster as a screening model for antiseizure medications - Fischer, Florian P.; Karge, Robin A.; Koch, Henner; Voigt, Aaron; Weber, Yvonne G.; Wolking, Stefan (Frontiers in Pharmacology, 2024)
Objective Resistance to antiseizure medications (ASMs) is a major challenge in the treatment of patients with epilepsy. Despite numerous newly marketed ASMs, the proportion of drug-resistant people with epilepsy has not significantly decreased over the years. Therefore, novel and innovative seizure models for preclinical drug screening are highly desirable. Here, we explore the efficacy of a broad spectrum of ASMs in suppressing seizure activity in two established Drosophila melanogaster bang-sensitive mutants. These mutants respond with seizures to mechanical stimulation, providing a promising platform for screening novel ASMs. Methods Seven frequently used ASMs (brivaracetam, cenobamate, lacosamide, lamotrigine, levetiracetam, phenytoin, and valproate) were administered to the bang-sensitive mutants easily shocked2F (eas2F) and paralyticbss1 (parabss1). After 48 h of treatment, the flies were vortexed to induce mechanical stimulation. The seizure probability (i.e., ratio of seizing and non-seizing flies) as well as the seizure duration were analyzed. Results In case of eas2F mutants, treatment with the sodium channel blockers phenytoin and lamotrigine resulted in a robust reduction of seizure probability, whereas flies treated with lacosamide showed a decrease in seizure duration. Treatment with valproate resulted in both a reduction in seizure probability and in seizure duration. In contrast, levetiracetam, brivaracetam and cenobamate had no effect on the bang-sensitive phenotype of eas2F flies. In case of parabss1 flies, none of the tested medications significantly reduced seizure activity, supporting its role as a model of intractable epilepsy. Significance Our results show that particularly sodium channel blockers as well as valproate are effective in suppressing seizure activity in the bang-sensitive mutant eas2F. These findings demonstrate the usability of Drosophila for screening drugs with antiseizure properties. Due to fewer ethical concerns, the short life cycle, and low maintenance costs, Drosophila might provide an attractive and innovative high-throughput model for the discovery of novel antiseizure compounds.